2021
DOI: 10.3390/md19100563
|View full text |Cite
|
Sign up to set email alerts
|

Potential Biomedical Applications of Collagen Filaments derived from the Marine Demosponges Ircinia oros (Schmidt, 1864) and Sarcotragus foetidus (Schmidt, 1862)

Abstract: Article [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 55 publications
2
12
0
Order By: Relevance
“…Collagen, the most abundant fibrous protein, is found within hard and soft tissues, such as connective tissue [126], skin [127][128][129], tendon [130], cornea [131], and cartilage [132][133][134][135], and is a crucial constituent of the ECM [136]. In this regard, collagen derived from the bovine [137], porcine [138], fish [139], marine sponge [140], shellfish [141], and jellyfish [142] is largely explored, so as to be utilized as a biocompatible material in various fields [143].…”
Section: Collagen-based Hydrogelsmentioning
confidence: 99%
“…Collagen, the most abundant fibrous protein, is found within hard and soft tissues, such as connective tissue [126], skin [127][128][129], tendon [130], cornea [131], and cartilage [132][133][134][135], and is a crucial constituent of the ECM [136]. In this regard, collagen derived from the bovine [137], porcine [138], fish [139], marine sponge [140], shellfish [141], and jellyfish [142] is largely explored, so as to be utilized as a biocompatible material in various fields [143].…”
Section: Collagen-based Hydrogelsmentioning
confidence: 99%
“…However, skin and bones from bovine or porcine wastes continues to be the primary source of proteins for regenerative medicine. Recently, the scientific community has shown a strong interest in the marine collagen isolated from fish and various marine invertebrates, including sponges, used in tissue engineering [121,122]. Collagen extracts from Chondrosia reniformis (Nardo, 1847) do not cause toxicity in mammalian cells, but positive effects on the proliferation of L929 fibroblasts, HaCat keratinocytes and RAW 264.7 macrophages.…”
Section: Other Miscellaneous Activitiesmentioning
confidence: 99%
“…So, these data suggested that extracts could be exploited for cosmetic or regenerative medicine purposes, facilitating cell migration or proliferation at the site of the wounded epidermal and dermal cells [121]. Pozzolini et al [122] isolated collagen filaments from the marine sponges Ircinia oros and Sarcotragus foetidus (Schimdt, 1862), collected in the Ligurian Sea, and tested them on HaCat keratinocytes and L929 fibroblasts. Additionally, in this study, the extracts were effective for wound-healing when compared with the positive controls hydrogen peroxide and quartz.…”
Section: Other Miscellaneous Activitiesmentioning
confidence: 99%
“…These issues demonstrate a need for an alternative source of collagen and biomaterials. Marinederived biomaterials including chitin and alginate have demonstrated the benefits of marine biomaterials [3,4], and more recently collagens from marine sources have attracted great interest as biomaterials due to their biocompatibility, high biodegradability, low immunogenicity and ease of extraction [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%